1976
DOI: 10.1021/ja00425a033
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical transformations of small ring heterocyclic compounds. 75. Photochemistry of arylazirines in hydroxylic media

Abstract: Irradiation of substituted arylazirines produces nitrile ylides which react with methanol to give methoxyimines in excellent yield. Deuterium labeling studies indicate that the electron density is highest on the disubstituted carbon atom of the nitrile ylide formed on irradiation. With this conclusion, all of the regiochemical data found in the photoaddition of arylazirines with electron-deficient dipolarophiles can be explained by use of the frontier orbital method. The addition of alcohol to nitrile ylides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…This procedure has been widely used in the synthesis of a variety of five-membered heterocycles (cf., Scheme 1). [5][6][7][24][25][26][27] Recent quantum-chemical calculations shed some light on the above-mentioned observations. On the basis of complete active space self-consistent field (CASSCF) calculations, Klessinger and Borneman 28,29 demonstrated that the photochemical formation of the nitrile ylide from the respective 2H-azirine (by C-C bond cleavage) occurs in an nπ* singlet excited state and involves a barrierless conical intersection between the S 1 and S 0 potential energy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been widely used in the synthesis of a variety of five-membered heterocycles (cf., Scheme 1). [5][6][7][24][25][26][27] Recent quantum-chemical calculations shed some light on the above-mentioned observations. On the basis of complete active space self-consistent field (CASSCF) calculations, Klessinger and Borneman 28,29 demonstrated that the photochemical formation of the nitrile ylide from the respective 2H-azirine (by C-C bond cleavage) occurs in an nπ* singlet excited state and involves a barrierless conical intersection between the S 1 and S 0 potential energy surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the in-situ generated nitrile ylide can be trapped intramolecularly by a nucleophile such as a hydroxy group [25]. This is demonstrated by the photochemical degradation of vinyl azide 1g which yielded 2,5-dihydrooxazole 9 in 76% yield ( c = 0.01 M, flow rate = 0.02 mL/min) under flow conditions (Scheme 7).…”
Section: Resultsmentioning
confidence: 99%
“…Under photochemical conditions, the highly strained 2 H -azirines 29 underwent ring-opening to yield the nitrile ylides 42 . 20 These 1,3-dipolar intermediates proved to be excellent [3 + 2] cycloaddition substrates for dipolarophiles 43 . The cyclization provided 3,4-dihydro-2 H -pyrroles 44 in reasonable yields (Scheme 8).…”
Section: Thermal- or Photo-induced Reactions Of Vinyl Azidesmentioning
confidence: 99%